Reception. (October 2021) - Bridges, Emma; Stead, Henry
Abstract : From Oxford University Press's 'Classical Presences' series, Carol Dougherty's Travel and Home in Homer's Odyssey and Contemporary Literature places Homer's Odyssey in dialogue with five twentieth- and twenty-first-century novels which all deal in some way with the ideas of home or travel. The author focuses on novels which, on the whole, do not respond overtly to the Odyssey, but which instead share key themes – such as transience, reunion, nostalgia, or family relationships – with the Homeric poem. The conversations which she initiates between the ancient epic and the modern novels inspire us to rethink previously held assumptions about the Odyssey . For example, Dougherty's exploration of Rebecca West's The Return of the Soldier (1918), in which a veteran returns from the First World War with no memory of his wife, prompts her reader to consider Odysseus' stay with Calypso as 'a kind of nostalgic amnesia, a necessary break that enables rather than an obstacle that impedes his return' (111). As 'an experiment in improvisatory criticism' (16), this book yields rich rewards for the reader who is already familiar with the Odyssey, as well as for those whose point of entry is one of the five modern novels. The framework applied – in which each chapter presents a reading of a relevant section of the Odyssey before setting out an analysis of the contemporary novel with which it is paired – is perhaps more familiar from comparative literary studies than from classical reception scholarship, yet Dougherty's approach is one which stimulates fresh thought about how we as readers (re-)interpret and 'receive' ancient texts based on the contexts in which we encounter them.